Ionic liquids as electrolytes in aluminum electrolysis - Wu, Junshi; Xie, Peng; Hao, Wenbin; Lu, Dong; Qi, Ye; Mi, Yongli (Frontiers in Chemistry, 2022)
Herein, the characteristics, research progress, and application prospects of ionic liquid-based electrolytic aluminum deposition are reviewed and analyzed in comparison with the Hall–Héroult method. The reaction conditions and production procedures of this material are discussed alongside the problems ionic liquids face in the electrolytic aluminum industry. Ionic liquid-based electrolytic aluminum deposition realizes the electrolytic aluminum reaction at low temperatures, achieving a reaction energy consumption close to the theoretical minimum value. The reaction also avoids harmful CO2 or HF emissions, demonstrating a green and environmental-friendly approach to the production of electrolytic aluminum. In the future, in-depth work on the implementation of ionic liquid electrolytes should be carried out, establishing the necessary technical criteria and laying the foundation for the integration of this approach.